IndiGo - In the Times of Pandemic - Narender, M.; Arun Kumar, A. (Indian Journal of Finance, 2021)
Over the years now, the Indian aviation has seen a lot of difficulties, and recently, the players in aviation started working towards competing with global players in the industry in terms of quality of service and making the balance sheet look stronger. All this enthusiasm boiled down due to the COVID-19 pandemic, which impacted all the economies across the globe. This pandemic has thrown a lot of challenges like whopping decrease in the revenues but not the costs to the same extent, uncertain changes in the regulations by the state governments on imposing quarantine for the domestic passengers, which resulted in impacting the survival of some of the weak players. IndiGo suffered its biggest losses since it went public in the year 2015, and these losses can be attributed to the pandemic. However, there are certain measures that can be put in place sooner rather than later. These are to do with attracting other forms of services like cargo and access to competent and quick investors to pump in capital. These twin factors must be the subject of urgent policy measures for IndiGo to be ahead of the pack.